Implementasi Hukum Tata Negara pada Pemilihan Kepala Daerah dalam Pandemi Virus Corona 2019 (Covid -19) - Yustiana Dwirainaningsih; Salman Al Farasi (JURNAL LITBANG KOTA PEKALONGAN, 2021)
The speread of Corona Virus Disease 2019 (COVID-19) as a non-natural national disaster requires handling policies and extraordinary steps both at the central and regional levels including the need to postpone the implementation stages of the election for gove rnors and deputy governors, regents and deputy regents, as well as mayors and deputies Concurrent mayor in 2020. The implementation of regional head elections has the aim that the election for governors and deputy mayors can continue in a democratic and quality manner and to maintain domestic political stability, on the orther hand health is maintained by strict health protocol at everystage of selection. The impact of the non-natural disaster pandemic Corona Virus Disease (Covid-19) wich occurred several moths ago resulted in the simultaneous Regional Head Election which was originally scheduled for September 2020 to be postponed to December 2020 in accordance with the issuance of a Government Regulation in Lieu Of Law Number 2 of 2020 wich is technically made by the General Election Commissions. General Election Commissions Regulation Number 6 of 2020.T he research method uses the normative legal writing method and aims to provide on explanarion regarding the contitusional law perspective on the implementati on of simultaneous regional head election in the mudst of a non-natural disaster pandemic Corona virus Deisease (Covid-19). The research results are expected to contribute to scientific development in the field of law. Keywords: Implementation of Constitutional Law, Regional Head Elections, Corona Pandemic Virus Disease (Covid-19)